The Beliefs, Myths, and Reality Surrounding the Word Hema (Blood) from Homer to the Present. (6th June 2010) - Meletis, John; Konstantopoulos, Kostas
Abstract : All ancient nations hinged their beliefs about hema (blood) on their religious dogmas as related to mythology or the origins of religion. The Hellenes (Greeks) especially have always known hema as the well-known red fluid of the human body. Greek scientific considerations about blood date from Homeric times. The ancient Greeks considered hema as synonymous with life. In Greek myths and historical works, one finds the first references to the uninterrupted vascular circulation of blood, the differences between venous and arterial blood, and the bone marrow as the site of blood production. The Greeks also speculated about mechanisms of blood coagulation and the use of blood transfusion to save life.